Sevoflurane promotes premature differentiation of dopaminergic neurons in hiPSC-derived midbrain organoids - Shang, Jia; Li, Bin; Fan, Han; Liu, Peidi; Zhao, Wen; Chen, Tao; Chen, Pu; Yang, Longqiu (Frontiers in Cell and Developmental Biology, 2022)
Background: Conventional animal models used in the corresponding basic studies are distinct from humans in terms of brain development trajectory, tissue cytoarchitecture and cell types, making it difficult to accurately evaluate the potential adverse effects of anesthetic treatment on human fetal brain development. This study investigated the effects of sevoflurane on midbrain development and cytopathology using human physiologically-relevant midbrain organoids. Methods: In this study, monolayer human induced pluripotent stem cells (hiPSC) -derived human floor plate cells (hFPCs) and three-dimensional hiPSC -derived midbrain organoids (hMBOs) were exposed to 2% (v/v) sevoflurane for 2 or 6 hours, followed by expansion or differentiation culture. Finally, immunofluorescence, Real-time PCR, EdU assay, Tunnel assay and transcriptome sequencing were used to examine the effects of sevoflurane on midbrain development. Results: (i) 2% sevoflurane exposure inhibited hFPC proliferation (7.2%±0.3% VS 13.3%±0.7%, P=0.0043 in the differentiation culture; 48%±2.2% VS 35.2%±1.4%, P=0.0002 in the expansion culture) and increased hFPC apoptosis, but did not affect differentiation of hFPCs into human dopaminergic neurons (hDANs); (ii) 6-hour 2% sevoflurane exposure inhibited cell proliferation (62.8%±5.6% VS 100%±5.5%, P=0.0065) and enhanced premature differentiation of hMBOs (246%±5.2% VS 100%±28%, P=0.0065). Conclusion: This study showed that the long-term exposure to sevoflurane promotes premature differentiation of hMBOs while the short-term exposure to sevoflurane has a negligible effect on the differentiation of hMBOs. These results imply that long-term exposure to sevoflurane in pregnant women may lead to fetal midbrain development disorder.